Senior Woman Administrators' Perceptions and Experiences of Women Serving in Leadership Positions in Conference Offices - Kelly Patricia Elliott; Tim Kellison (Journal of Applied Sports Management, 2020)
NCAA conference office Senior Woman Administrators (SWAs) were surveyed to gain their perspective on the gender disparity reported in intercollegiate athletics. The perceptions offered by the SWAs indicate the need for NCAA conference offices to implement professional development programming for women aimed at increasing management skills, developing best practice guidelines for including SWAs in athletic administration, and establishing mentor programs for women working on member institution campuses. Additionally, the results indicate directors of athletics need to create more meaningful opportunities for women to participate in decision making and include SWAs in meetings with coaches and other staff members.
Keywords: Intercollegiate Athletics; Organizational Behavior; Sport; Social Role Theory